Response of Pear Fruit Cv. Butirra Precoce Morettini to Kmno4, Bread Yeast at Two Storage Periods. - AL-Bamarny, Sarfaraze F. A.; Bani, Shukri H. S.; Mohamad, Abulrahman A. (Science Journal of University of Zakho, 2015)
This study was carried out on fruits of five years old pear trees (Pyrus communis L) in the central laboratory in Agricultural Faculty/ Duhok University / Iraqi Kurdistan Region, during growing season 2012, to investigate the effect of potassium permanganates (KMnO4), bread yeast and storage periods on fruit storage behavior of Butirra Precoce Morettini pear fruit. The results revealed that the fruit treated with 10 g KMnO4 / bag increased significantly the firmness but the weight loss percent was significantly decreased. Also fruit dipped in 4% bread yeast caused a significant increase in weight loss percent, juice volume and juice percent. Whereas TSS, firmness, juice percent, total sugars and total acidity were decreased as storage prolonged from 56 days to 127 days, except weight loss percent which increased significantly during the same storage periods. The effect of the interaction between KMnO4 and bread yeast levels with storage periods was significant. The interaction between 20g KMnO4 /bag and 56 days storage resulted in the highest fruit firmness, but the best interaction in decreasing weight loss was 10g KMnO4 /bag with 56 days storage. On the other hand, the interaction between 20g KMnO4 /bag with 127 days storage gave the lowest acidity. Concerning the increasing of ascorbic acid in fruits, the best interaction was 20g KMnO4 /bag with 127 days storage.